Exploring the Perceptions of Student Prisoners on Challenges with Supervisors in Prison Education - Mahlangu, Vimbi Petrus (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2024)
This study examines the challenges faced by incarcerated students in their interactions with study supervisors within prison education programs in Namibia. Using a qualitative design and an interpretive paradigm, semi-structured interviews with 12 male participants were analyzed thematically to uncover key barriers in the student-supervisor dynamic. Findings highlight systemic issues, including limited technological access, communication barriers, and insufficient supervisory support, which hinder effective learning and engagement. Participants emphasized the psychological impact of delayed feedback, restricted access to study materials, and a lack of supervisor understanding of educational needs. These insights underscore the need for enhanced training for supervisors, improved communication infrastructure, and equitable access to digital resources to create supportive learning environments in correctional facilities. By addressing these barriers, the study contributes to improving educational outcomes and supports broader rehabilitative efforts for incarcerated learners.